2018
DOI: 10.1002/aah.10040
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Whirling‐Disease‐Resistant Rainbow Trout Fry in the Wild: A Comparison of Two Strains

Abstract: Introduced pathogens can affect fish populations, and three main factors affect disease occurrence: the environment, host, and pathogen. Manipulating at least one of these factors is necessary for controlling disease. Myxobolus cerebralis, the parasite responsible for salmonid whirling disease, became established in Colorado during the 1990s and caused significant declines in wild Rainbow Trout Oncorhynchus mykiss populations. Attempts to re-establish Rainbow Trout have focused on manipulating salmonid host re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…M. cerebralis was introduced to Colorado in the late 1980s, and later found in free‐ranging salmonid populations in 11 of the state's 15 major river drainages (Barney et al., 1988; Nehring & Thompson, 2003), resulting in the collapse of wild rainbow trout populations throughout Colorado (Nehring & Thompson, 2001). The state of Colorado has been using M. cerebralis ‐resistant rainbow trout to re‐establish populations in the presence of the parasite (Avila et al., 2018; Fetherman et al., 2014), and reproduction and recruitment are occurring (Fetherman et al., 2014). Stocking F. psychrophilum ‐resistant fish with no resistance to M. cerebralis could result in failure due to mortality associated with M. cerebralis exposure, as well as increased infection severity and loss of progress gained from M. cerebralis ‐resistant rainbow trout stocking efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. cerebralis was introduced to Colorado in the late 1980s, and later found in free‐ranging salmonid populations in 11 of the state's 15 major river drainages (Barney et al., 1988; Nehring & Thompson, 2003), resulting in the collapse of wild rainbow trout populations throughout Colorado (Nehring & Thompson, 2001). The state of Colorado has been using M. cerebralis ‐resistant rainbow trout to re‐establish populations in the presence of the parasite (Avila et al., 2018; Fetherman et al., 2014), and reproduction and recruitment are occurring (Fetherman et al., 2014). Stocking F. psychrophilum ‐resistant fish with no resistance to M. cerebralis could result in failure due to mortality associated with M. cerebralis exposure, as well as increased infection severity and loss of progress gained from M. cerebralis ‐resistant rainbow trout stocking efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The state of Colorado has been using M. cerebralis-resistant rainbow trout to re-establish populations in the presence of the parasite (Avila et al, 2018;Fetherman et al, 2014), and reproduction and recruitment are occurring (Fetherman et al, 2014). Stocking F. psychrophilum-resistant fish with no resistance to M. cerebralis could result in failure due to mortality associated with M. cerebralis exposure, as well as increased infection severity and loss of progress gained from M. cerebralis-resistant rainbow trout stocking efforts.…”
mentioning
confidence: 99%
“…Avila et al . ( 2018 ) showed that the stream characteristics in systems in which M. cerebralis was present or absent affected the survival of two M. cerebralis– resistant strains of O. mykiss , stocked as fry, 2 months after stocking. The presence of other species may also affect stocking success.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of other species may also affect stocking success. Previous work has shown that brown trout Salmo trutta L. competition with O. mykiss results in the exclusion of O. mykiss fry from desired habitats (Gatz et al ., 1987 ), and fry stocking success may be affected by predation from larger S. trutta (Avila et al ., 2018 ). Although mechanical removals may be an option for reducing competition and predation between stocked O. mykiss and S. trutta , removals can be both time intensive and expensive (Fetherman et al ., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation